(Co)isotropic Pairs in Poisson and Presymplectic Vector Spaces - Lorand, J.; Weinstein, А. (Symmetry, Integrability and Geometry: Methods and Applications, 2015)
We give two equivalent sets of invariants which classify pairs of coisotropic subspaces of finite-dimensional Poisson vector spaces. For this it is convenient to dualize; we work with pairs of isotropic subspaces of presymplectic vector spaces. We identify ten elementary types which are the building blocks of such pairs, and we write down a matrix, invertible over Z, which takes one 10-tuple of invariants to the other.